The New German Law on Sexual Assault and Sexual Harassment. Issue 6 (1st November 2017) - Hörnle, Tatjana
Abstract : In 2016, the German parliament changed the law on sexual assault and rape (Sect. 177 StGB). The new law assumes a "no-means-no"-model, while the old law required coercion as a necessary feature of rape and other forms of sexual assaults. In addition, two new offense descriptions were introduced: sexual harassment (Sect. 184i StGB) and offenses out of groups (Sect. 184j StGB). In this Article, I describe the deficiencies of the old law, the process of law reform, and the newly enacted prohibitions.